ОЛИЙ ПЕДАГОГИК ТАЪЛИМ МУАССАСАЛАРИДА АХБОРОТ ТАЪЛИМИ МУҲИТИДАН ФОЙДАЛАНИШНИНГ ПЕДАГОГИК ШАРТЛАРИ - Тайлаков, У.Н. (SCIENCE and SOCIETY, 2016)
The article is devoted to the ussues of formation of pedagogical conditions for using informational-educational environment at higher pedagogical educational institutions.